A PLAN FOR HANDLING COMPLEX FINANCING IN KPR PRODUCT: BANK JATIM SYARIAH - Wahyuni, Hana; Nasrulloh (NISBAH: Jurnal Perbankan Syariah, 2023)
The need for adequate housing continues to increase very rapidly from year to year along with the increase in population, but there are still many obstacles to fulfilling it. So banking institutions are present as intermediation institutions by offering mortgage financing products. Due to the large number of applications for financing, problems often arise. This research aims to determine the factors that cause financing problems in the iB Barokah KPR product at Bank Jatim Syariah Jombang evidence. The research method used is a qualitative descriptive research method. Data collection techniques come from interviews and observations. The results of this research show that the factors that cause financing problems with the iB Barokah KPR product are caused by external factors (the customer's side) whether caused by intentional or unintentional elements, such as customers affected by natural disasters, the Covid-19 pandemic, and bad customer character. The strategy used to deal with the risk of problematic financing goes through three stages. First, the stage of anticipating problematic financing by conducting a 5C analysis and a psychological approach. Second, the rescue stage user restructuring. Third, the settlement stage is through non-litigation, litigation.